Meteoritic ablation debris from the Transantarctic Mountains: Evidence for a Tunguska-like impact over Antarctica ca. 480 ka ago - Van Ginneken, M.; Folco, L.; Perchiazzi, N.; Rochette, P.; Bland, Phil (Elsevier Science BV, 2010)
Aggregates of microscopic spherules broadly similar in texture and composition to cosmic spherules or meteorite ablation spheres were discovered within the ∼ 1 Ma-old Transantarctic Mountain micrometeorite traps at Miller Butte, Victoria Land, Antarctica. Mineralogical and geochemical data obtained by means of field emission-scanning electron microscopy, electron microprobe analyses, synchrotron X-ray diffraction, and magnetization measurements show that they consist of a porous aggregate of quench-textured spherules, with individual spherules ranging from less than 1 to 65 µm in diameter. Spherule types include porphyritic olivine plus magnesioferrite spherules, dendritic magnesioferrite spherules, barred and feathered olivine spherules, and cryptocrystalline spherules. In contrast to the textural variations, the bulk composition of the individual spherules is fairly homogeneous and broadly chondritic. Likewise olivine has a nearly homogeneous composition Fa16.3 ± 2.7. Olivine and magnesioferrite are characterized by high NiO contents (2.72 ± 1.6 and 4.68 ± 0.68 wt.%, respectively), as typically observed in ablation debris and meteorite fusion crusts. The bulk composition of the aggregates is similar to the fusion crust of ordinary and carbonaceous chondrites.We interpret the spherulitic aggregates as meteorite ablation debris formed during the atmospheric entry of a large meteorite of ordinary or carbonaceous chondritic composition. Comparison with the available literature data shows that the ablation debris found at Miller Butte is most likely paired with the extraterrestrial dust found in a ~ 480 ka-old ice layer in the EPICA-Dome C and Dome Fuji ice cores (East Antarctic ice sheet), thereby documenting a continental-scale distribution of ablation debris associated with a major meteoritic impact event which occurred ~ 480 ka ago. Based on estimates of the projectile mass (> 108 kg) and numerical simulation of small-scale impacts from literature, we propose that the continental-scale distribution of the ablation debris was generated by the deceleration of a giant impact plume associated with a Tunguska-like impact over Antarctica. Tunguska-like impacts have global frequencies on the order of 103 to 105 yr, consistent with several being recorded in the Antarctic ice sheet. Finally, our detailed petrographic description of the spherulitic aggregates could serve as guide to the search for Tunguska-like events in the geological record.